Ответ:
a) A = -36, [tex]B=\dfrac{2}{9}[/tex]
b) A·B + 4 = -4
Пошаговое объяснение:
a) A = -1-2-3-4-5-6-7-8 = -(1+2+3+4+5+6+7+8) = -((1+8)+(2+7)+(3+6)+(4+5)) =
= -(9+9+9+9) = -4·9 = -36.
[tex]\displaystyle B=\left (-\frac{1}{2} \right ) \cdot \left (-\frac{2}{3} \right ) \cdot \left (-\frac{3}{4} \right ) \cdot \left (-\frac{8}{9} \right ) = \frac{1 \cdot 2 \cdot 3 \cdot 8}{2 \cdot 3 \cdot 4 \cdot 9} = \frac{2 \cdot 3 \cdot 4 \cdot 2}{2 \cdot 3 \cdot 4 \cdot 9} = \frac{2}{9}.[/tex]
[tex]\displaystyle \tt b) \; \tt A \cdot B+4 = -36 \cdot \frac{2}{9}+4 = \frac{-36 \cdot 2}{9}+4 =\frac{-4 \cdot 9 \cdot 2}{9}+4 =-4 \cdot 2+4 = -8+4 = -4.[/tex]
#SPJ1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
a) A = -36, [tex]B=\dfrac{2}{9}[/tex]
b) A·B + 4 = -4
Пошаговое объяснение:
a) A = -1-2-3-4-5-6-7-8 = -(1+2+3+4+5+6+7+8) = -((1+8)+(2+7)+(3+6)+(4+5)) =
= -(9+9+9+9) = -4·9 = -36.
[tex]\displaystyle B=\left (-\frac{1}{2} \right ) \cdot \left (-\frac{2}{3} \right ) \cdot \left (-\frac{3}{4} \right ) \cdot \left (-\frac{8}{9} \right ) = \frac{1 \cdot 2 \cdot 3 \cdot 8}{2 \cdot 3 \cdot 4 \cdot 9} = \frac{2 \cdot 3 \cdot 4 \cdot 2}{2 \cdot 3 \cdot 4 \cdot 9} = \frac{2}{9}.[/tex]
[tex]\displaystyle \tt b) \; \tt A \cdot B+4 = -36 \cdot \frac{2}{9}+4 = \frac{-36 \cdot 2}{9}+4 =\frac{-4 \cdot 9 \cdot 2}{9}+4 =-4 \cdot 2+4 = -8+4 = -4.[/tex]
#SPJ1